The Quantum microRNA Immunity in Human Virus-Associated Diseases: Virtual Reality of HBV, HCV and HIV-1 Infection, and Hepatocellular Carcinogenesis with AI Machine Learning - Fujii, Yoichi Robertus (Archives of Clinical and Biomedical Research, 2020)
Objectives: Since virus-related hepatocellular carcinoma (HCC) is quite complexed, the etiology of virus-associated HCC is remained unclear. We have previously shown that the microRNA (miRNA) entangling sorter (METS) analysis with quantum miRNA/miRNA language is available for the etiology investigation in silico from miRNA biomarker panels of human cancers to predict carcinogenesis. To further investigate the etiology of human virus-associated diseases on the stage minus one (zero), host-virus miRNA interactions were investigated by computer simulation on METS analysis with artificial intelligence (AI) machine learning (MIRAI). Materials and Methods: The information of the miRNA biomarker panels in hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency virus type 1 (HIV-1) infection, virus-related fibrosis (cirrhosis), and virus-associated HCCs was extracted from database. The miRNA hub in the panels was selected by both protein/protein interaction and carcinogenic protein function. The statistical analysis upon tumorigenesis was calculated by Prediction One. Results: The etiology of infection, fibrosis or HCC was simulated by METS analysis with host miRNAs and viral miRNAs. Quite different strategy was shown as the host defense against HBV, HCV and HIV-1 infection under controlled by host miRNAs and viral mRNAs. HBV and HIV-1 was defensed by cell death through shutdown and cell cycle arrest, respectively. HCV was prevented by inhibition of virus production. Carcinogenesis by HBV was induced by repeated wound-healing in fibrosis (cirrhosis) programmed by host miRNA information, and host and viral miRNAs were implicated in tumorigenic activity upon HCV infection. Conclusions: We found the third host defense neomechanism, named ‘the quantum miRNA immunity’ against human virus-related diseases.</